Efektivitas Fitoremediasi Menggunakan Eceng Gondok (Eichhornia crassipes) dalam Mengurangi Kadar BOD dan COD pada Air Lindi TPA Tamangapa, Kota Makassar - Sahani, Wahyuni; Kasim, Khiki Purnawati; Syarif , Andi Muhammad (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2025)
Leachate is a liquid that seeps through waste piles, containing suspended matter. The existence of this leachate water is a source of problems, as well as the Tamangapa landfill which produces an increasing amount of leachate water and is a risk to the community around the Tamangapa landfill. The research applied was a quasi experimental design using eceng media with a pre-test-post test design using 3 media variations, 5 clumps, 10 clumps, and 15 clumps. The results showed that the decrease in BOD and COD levels in leachate water showed a decrease with a variation of 5 clumps reducing BOD levels by 411.20 mg/l (33.07%) while COD by 1048.53 mg/l (36.81%). For 10 clumps, the BOD level decreased by 231.46 mg/l (62.33%) while COD by 589.40 mg/l (63.92%). And 15 clumps reduced BOD levels by 233.73 mg/l (61.87%) while COD by 603.16 mg/l (63.71%). These results show that the use of phytoremediation methods with media variations of 5 clumps, 10 clumps, and 15 clumps can reduce BOD and COD levels in leachate water but have not been able to reduce to the predetermined threshold.